2000
DOI: 10.1002/1097-0134(20001201)41:4<485::aid-prot60>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations between stabilizing and destabilizing electrostatic contributions of ion pairs in conformers of the c-Myc-Max leucine zipper

Abstract: In solution proteins often exhibit backbone and side‐chain flexibility. Yet electrostatic interactions in proteins are sensitive to motions. Hence, here we study the contribution of ion pairs toward protein stability in a range of conformers which sample the conformational space in solution. Specifically, we focus on the electrostatic contributions of ion pairs to the stability of each of the conformers in the NMR ensemble of the c‐Myc‐Max leucine zipper and to their average energy minimized structure. We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…Salt bridges with favorable geometrical positioning of the interacting side chain charged groups are likely to stabilize the protein structure. These observations have gained further support from our recent work in this direction [90,91,Kumar and Nussinov, unpublished data].…”
Section: Protein Thermostability and Electrostatic Interactionssupporting
confidence: 52%
See 1 more Smart Citation
“…Salt bridges with favorable geometrical positioning of the interacting side chain charged groups are likely to stabilize the protein structure. These observations have gained further support from our recent work in this direction [90,91,Kumar and Nussinov, unpublished data].…”
Section: Protein Thermostability and Electrostatic Interactionssupporting
confidence: 52%
“…Protein flexibility is essential for function. Our recent investigations into the role of electrostatic interactions in systemic protein flexibility [90,91] have shown that salt bridges and their networks observed in protein crystal structures may easily break and reform in CMLS, Cell. Mol.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Interhelical ion pairs have been described as either having no effect on stability or being slightly destabilizing25, 49, 50 or being stabilizing 51, 52. The electrostatic free energy of salt bridges was shown to change sign at least once across 40 NMR conformers of the c‐Myc‐Max leucine zipper 53. From the analysis of a large set of ion pairs, it was concluded that stabilizing or destabilizing effects are governed not only by the mutual geometrical orientation of the participating charged groups but are also very sensitively dependent on the exact distribution of full and partial charges in the protein matrix 54.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of multiple protein structures for the same protein is valuable in studying protein flexibility. In our studies,2b,2c we have used NMR conformer ensembles and protein crystal structures to study systemic protein flexibility. Figure 1 provides an example of protein flexibility and illustrates individual conformers in the NMR conformer ensemble of the Escherichia coli chemotaxis protein CheY as well as its crystal structures.…”
Section: Specific Interactions and Protein Flexibilitymentioning
confidence: 99%
“…All the ion pairs and the ion‐pair network show extensive conformer‐dependent fluctuations in their electrostatic strengths and geometries, as well as the location of the charged residues. However, the most surprising observation was that each ion pair, as well as the ion pair network (IPN‐5), interconverted between being stabilizing and being destabilizing 2b. This indicates that the overall electrostatic contribution of the ion pairs toward proteins is conformer‐population dependent.…”
Section: Free Energy Contribution Of Electrostatic Interactions Tomentioning
confidence: 99%